Study of the kinetics of the recrystallization of cold-rolled low-carbon steel - Rodríguez Torres, Claudia Elena (2002)
The suitability of the differential scanning calorimetry (DSC) technique for the quantitative study of the recrystallization process in cold-rolled steels is demonstrated, the recrystallization kinetics was described with a semiempirical model, and the transformation of a cold-rolled steel submitted to an industrial-batch thermal cycle was appropriately simulated. It was found that the activation energy for the recrystallization process depends on the heating-rate range, having values of 522 ± 13 and 259 ± 12 kJ/mole for low and high heating rates, respectively. It was concluded that the smallest value corresponds to the recrystallization process alone, while the largest one contains an additional contribution from the aluminium nitride precipitation. It is also shown that the X-ray diffraction (XRD) line-width measurement is a useful complementary method to determine the temperature regions where recovery and recrystallization occur.